Self-Regulated Learning and Online Game Addiction in College Student - Eugenius Vercelly Hamaer Lotar Lejap; R. Pasifikus Ch. Wijaya; Marselino K. P. Abdi Keraf (Universitas Nusa Cendana, 2022)
This study aims to determine the relationship between self-regulated learning and online game addiction. This research is quantitative research with Spearman correlation. The number of subjects in this study was 337 people. The sampling technique used in this research is cluster sampling. The method of collecting data is quantitatively through an online questionnaire. The results showed no relationship between self-regulated learning and online game addiction. This study suggests not using self-regulation variables in learning because it cannot suppress online game addiction. It can be replaced using self-regulation, self-efficacy variables, and self-management. Teenagers who are indicated to be addicted to online games can immediately seek a psychologist so that their addiction can be reduced. Parents continue to support their children so that they can have good achievements and supervise children using smartphones, especially in playing online games, so that online game addiction does not occur.